Regresi Panel dalam Analisis Pengaruh Faktor Makroekonomi terhadap Harga Properti Residensial Tipe Kecil di 18 Kota Indonesia Tahun 2019–2024 - Amanah, Cici Nurhaliza; Yuniasih, Aisyah Fitri (Politeknik Statistika STIS, 2025)
Housing is a basic necessity that must be fulfilled by every individual. The 2020–2024 RPJMN targets increased access to adequate, safe, and affordable housing for Low-Income Communities (MBR). However, high property prices remain a major barrier. This study aims to analyze the factors influencing the prices of small-type residential properties in 18 cities in Indonesia during the 2019–2024 period. The small-type category was selected as it represents the MBR housing segment. The method used is panel data regression. The results show that GDRP per capita, GDRP deflator, and population density have a significant positive effect on the Small-Type Residential Property Price Index (IHPR), while the realization of FLPP subsidies has a significant negative effect. Meanwhile, the Construction Cost Index has no significant effect. These findings can serve as a basis for more targeted housing policies to meet the housing needs of low-income communities.